2022
DOI: 10.1007/s12144-022-03599-6
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and fathers of pre-school children: a study on parenting stress and child’s emotional-behavioral difficulties

Abstract: The present study aimed to analyze the differences between maternal and paternal parenting stress and children’s behavioral functioning, as determined by teacher and parent reports. In addition, it sought to evaluate the presence of clusters based on parenting stress and to determine whether perceptions of children’s behavioral functioning varied across these clusters. The sample was composed of the parents and teachers of N = 201 children. Parents completed a self-report questionnaire on parenting stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 83 publications
0
2
0
1
Order By: Relevance
“…Higher rates of maternal psychopathology might be explained by onerous work-family conflicts and additional multidimensional child care demands regularly experienced by mothers [52]. Additionally, mothers report higher parenting distress than fathers [53], which might also contribute to higher ratings of psychopathology. Further, male gender stereotypes of not admitting mental distress might play a role [54].…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of maternal psychopathology might be explained by onerous work-family conflicts and additional multidimensional child care demands regularly experienced by mothers [52]. Additionally, mothers report higher parenting distress than fathers [53], which might also contribute to higher ratings of psychopathology. Further, male gender stereotypes of not admitting mental distress might play a role [54].…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan penelitian menunjukkan bahwa anak-anak prasekolah dapat menjadi penyebab stres bagi ibu (Trumello et al, 2023;Ward & Lee, 2020). Namun, masih terbatas penelitian yang mengeksplorasi mengenai bagaimana terapi regulasi emosi secara khusus dapat membantu ibu mengelola stres yang berkaitan dengan anak prasekolah.…”
Section: Regulasi Emosi Mengacu Pada Kemampuanunclassified
“…One study on a cohort of heterosexual couples and their elementary school aged children in Milan, Italy, found that parental perception of their child's behavior varied according to their stress level [55]. Another study of children aged 3 to 6 years old in Italy noted that parents reported higher levels of child prosocial behavior compared the same child's teacher [56]. Since the Asenze Cohort Study measures SDQ prosocial scores of teachers at wave 2, we propose a follow-up sensitivity analysis comparing prosocial behavior scores from a teacher's response to that from the primary caregiver at wave 2 [35].…”
Section: Plos Onementioning
confidence: 99%